Promoting Malaysians to Spend on Health: What It Takes to Encourage Malaysians to Spend on Health Promotion?. - Yong, Kang Cheah (Universiti Kebangsaan Malaysia, 2013)
In light of the important role of health-promoting expenditure in health, the objective of this study was to investigate the socio-demographic determinants of health-promoting expenditure such as purchase of medical equipment and services, food supplements and health education services and products among Malaysian adults.